Problem-solving in suicide attempters. - Pollock, L; Williams, J (2004)
BACKGROUND: Recent research studies on the psychological processes underlying suicidal behaviour have highlighted deficits in social problem-solving ability, and suggest that suicide attempters may, in addition, be passive problem-solvers. The aim of this study was to examine problem-solving in suicide attempters (including passivity) and to see whether the deficits are mood-dependent. METHOD: Two groups, a suicide attempter group and a non-suicidal psychiatric control group completed measures of depression, hopelessness, suicidal ideation and social problem-solving ability shortly after admission, and again 6 weeks later. In addition, a non-psychiatric control group provided baseline data at a single time point. RESULTS: The suicide attempter group displayed poorer problem-solving ability than matched psychiatric controls and this difference persisted despite change in mood. However, although suicidal patients were more passive in their problem-solving style than non-psychiatric controls, they were not significantly more passive than psychiatric controls. Problem-solving did not change with improving mood. CONCLUSIONS: Although passivity is not unique to suicidal patients, in combination with the smaller number and less effective alternatives generated, it may increase vulnerability.